TROPHODYNAMIC ACCUMULATION OF BROMINATED FLAME RETARDANTS IN BIOTA OF JAKARTA BAY - Agus Sudaryanto; Tomohiko Isobe; Shinsuke Tanabe (Widyariset, 2012)
The level of contamination, bioaccumulation and potential trophic transfer of toxic pollutants known as brominated flame retardants (BFRs), such as polybrominated diphenyl ethers (PBDEs) and hexabromocychlododecanes (HBCDs), was examined in biota representing different trophic levels in Jakarta Bay. Various organisms were collected using several catching methods during July-August 2007 at eastern part of the bay and were analyzed for nitrogen (N) and carbon (C) stable isotopes, 14 PBDE congeners and three HBCD isomers using GC-C-IRMS, GC-MS and LC-MS/MS, respectively. Analysis of N and C indicated that the biota was composed by different trophic levels within the Jakarta Bay ecosystem. Concentrations of total PBDEs and total HBCDs varied according to species, ranged from 1.6 ng/g lipid wt. to 57 ng/g lipid wt. and below detection limit (nd) to 4.1 ng/g lipid wt, respectively. Furthermore, there was significant positive correlation between trophic level (TL) and concentration of PBDEs was found, but not HBCDs. Trophic Magnification Factors (TMF) values of PBDEs ranged 0.63–3.0 with only two congeners (BDE-47 and BDE–100) having TMFs greater than one.